A STUDY OF TEACHING METHODS USED BY PRE-SERVICE ENGLISH TEACHERS (Proceedings of the International Conference on Future of Education, 2018)
Pre-service teachers from the English Department, Faculty of Education, Suratthani Rajabhat University were prepared various teaching approaches and methods for their teaching practicum. Each method was possibly used under various considerations and purposes. This research was aimed to investigate the teaching methods used by pre-service teachers while practicing the teaching and also to study about the impacts on learners’ learning using those selected methods. The twenty participants were selected by purposive sampling. The observation forms were designed to gather data on teaching behaviors and learners’ learning behaviors. The semi-structured interview was used for individual interviews. The findings revealed that three majors of teaching methods including the Grammar Translation Method, Audio-Lingual Method, and Total Physical Response were used by the pre-service teachers. Interestingly, Total Physical Response and Audio-Lingual Method were mostly used in primary schools while the Grammar Translation Method was mostly found in secondary schools. The primary school learners merely learned with enthusiasm to imitate the language while the secondary school learners learned about the forms and structures to pass the exam. Supervising and coaching by supervisors were played an important role. Pre-service teachers should be closely supervised and trained to implement various teaching methods and approaches that including the teaching techniques for their teaching performance in order to maintain the positive impacts on their learners’ learning.
Keywords: teaching methods; pre-service English teachers; teaching practice; learners’ learning impacts